(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2022)
Work life balance is generally considered as an individual level concept that equates balance with a lack of conflict or incompatibility between the worker’s family and work roles. achieved in accordance with the predetermined roadmap. In the process of working from home during the last few semesters, there were many cases that said it was less effective because there was no condition or habit that required teachers to work from home. This article has several objectives, namely, first, to find out the effect of Work Life Balance on teacher work commitment. Second, knowing the work climate on the work commitment of teachers. Third, knowing the effect of work life balance and work climate on teacher work commitment. The research method used is quantitative research with a descriptive approach and using a questionnaire instrument by taking a sample of 50 teachers which means it is a saturated sample. The result of this study is that partially work life balance has a significant effect on teacher work commitment. The work climate partially has a significant effect on the work commitment of teachers. Work life balance and work climate simultaneously have a significant influence on the work commitment of teachers. Keywords: Antesedent of Work Life Balance